Adoption of multi – model Assignment Fuzzy to find Optimizing for the use of internet line in the Ministry of Science and Technlogy - جواد, لميعة باقر; حسن, زينب فليح (Journal of Economics and Administrative Sciences, 2018)
We have provided in this research model multi assignment  with  fuzzy function goal has been to build programming model is correct Integer Programming fogging  after removing the case from the objective function data and convert it to real data .Pascal triangular graded mean using Pascal way to the center of the triangular.The data processing to get rid of the case fogging which is surrounded by using an Excel 2007 either model multi assignment  has been used program LNDO to reach the optimal solution, which represents less than what can be from time to accomplish a number of tasks by the number of employees on the specific amount of the Internet, also included a search on some of the basic concepts in fuzzy logic and areas of use, as research has included three types of as models customization, assignment  triple 3_dimension Assignment Problem (3AP), and assignment  triple Almertb3_ dimension Planer Assignment Problem (3PAP), and assignment  multi Multidimensional Assignmen Problem (MAP) and has been to apply this experience to get the data in the Information Technology Department at the Ministry of Science and Technology.